Eigenvalue problems for a k-Hessian-type equation - Zedong Yang; Zhanbing Bai (Nonlinear Analysis)
In this work, we focus on the eigenvalue problem for a class of k-Hessian-type equations. Under some suitable assumptions, we first determine the intervals of the parameter for the existence of nontrivial radial solutions. To this aim, we apply the eigenvalue theory and Jensen inequality. Finally, the behavior of the solutions with respect to the parameter is analyzed via Guo’s fixed point theorem.